Design of Resources Monitoring and Controlling System on Aircraft Maintenance Project in XYZ MRO - Rachmatulloh, Yendy; Ginardi, Raden Venantius Hari (Institut Teknologi Sepuluh Nopember, 2020)
Maintenance Repair and Overhaul (MRO) XYZ is a company engaged in aviation / aviation, especially in aircraft maintenance. MRO XYZ can work on the maintenance of several types of aircraft and its components in accordance with the certification and permits owned by MRO XYZ. The vital aspects that must be regulated in an aircraft maintenance project include the engineer involved in the maintenance process and the manhours calculation system who must be able to explain every detail of the work on an aircraft maintenance project. In addition, other resources such as consumbale material and raw material must also be monitored and controlled, so that management team can obtain COGS as optimal as possible in the project and profitability can increase. This research was built to provide solutions to the aircraft maintenance process stakeholders in meeting vital information needs that must be continuously monitored and based on this information, the system built will be able to control the ongoing maintenance process of the aircraft, in accordance with regulations.